Muslim Learners' Self-Confidence Building in Public Spaces: Study of Cheerful Wednesday Program at SMP Negeri 7 Pekalongan - Istiani, Nurul; Firdaus, Arham Ali (TATHO: International Journal of Islamic Thought and Sciences, 2024)
The weak self-confidence of each individual and the challenges of life in the current millennial era greatly affect the quality of self in shaping the public mentality of Muslim students, especially in schools. This qualitative study uses a case study approach to describe the Wednesday Ceria program at SMP Negeri 7 Pekalongan in building the confidence of Muslim students in the public sphere. Data were collected through observation and interview. Data were analyzed through the stages of reduction, presentation and verification. This study confirms the existence of self-confidence dimensions of Muslim students in the cognitive aspect in the form of self-potential and creativity. Meanwhile, in the affective aspect in the form of enthusiasm and high socialization skills. The findings of this study confirm that Muslim learners' self-confidence in the public space can be manifested through Edutainment programs.